Factors Related to Fatigue among Chronic Kidney Disease Patients on Hemodialysis - Mailani, Fitri; Mansur, Arif Rohman; Rifdatunnisa, Aisyah; Chan, Chong Mei (Nurse Media Journal of Nursing, 2025)
Background: Fatigue is a common and distressing symptom among patients with chronic kidney disease (CKD) undergoing hemodialysis, significantly impacting their daily functioning and quality of life. Despite its prevalence, the contributing factors to fatigue remain unclear and underexplored in specific populations.Purpose: This study aimed to identify factors associated with fatigue among CKD patients undergoing hemodialysis.Methods: A cross-sectional study was conducted in two hemodialysis centers. A total of 164 patients were recruited using convenience sampling, with sample size determined through power analysis. Data were collected using the FACIT-Fatigue Scale, a health literacy questionnaire, and an observation sheet for hemoglobin (Hb), blood pressure, and interdialytic weight gain (IDWG). Patient characteristics were also recorded. T-tests and ANOVA were used to examine differences in fatigue levels across groups, while Spearman correlation and multiple linear regression were employed to analyze associations between fatigue and clinical variables.Results: The mean fatigue score was 28.23(SD=7.46). Fatigue was significantly associated with age, education level, employment status, comorbidities, duration of hemodialysis, systolic blood pressure, HB, IDWG, and health literacy (p<0.05). Multiple linear regression identified employment status and hemoglobin levels as the strongest predictors of fatigue.Conclusion: Fatigue is a prevalent issue among CKD patients undergoing hemodialysis and is influenced by a range of demographic, clinical, and behavioral factors. Employment status and hemoglobin levels were the most significant contributors. Interventions promoting physical activity, a healthy diet, and fluid adherence, alongside routine monitoring of hemoglobin levels, may help reduce fatigue and improve quality of life in this population.